L-leucine increases the sensitivity of drug-resistant Salmonella to sarafloxacin by stimulating central carbon metabolism and increasing intracellular reactive oxygen species level - Yang, Heng; Zhou, Yanhong; Luo, Qiong; Zhu, Chunyang; Fang, Binghu (Frontiers in Microbiology, 2023)
Introduction The overuse of antibiotics has made public health and safety face a serious cisis. It is urgent to develop new clinical treatment methods to combat drug resistant bacteria to alleviate the health crisis. The efficiency of antibiotics is closely related to the metabolic state of bacteria. However, studies on fluoroquinolone resistant Salmonella are relatively rare. Methods CICC21484 were passaged in medium with and without sarafloxacin and obtain sarafloxacin- susceptible Salmonella Typhimurium (SAR-S) and sarafloxacin resistant Salmonella Typhimurium (SAR-R), respectively. Non-targeted metabolomics was used to analyze the metabolic difference between SAR-S and SAR-R. Then we verified that exogenous L-leucine promoted the killing effect of sarafloxacin in vitro, and measured the intracellular ATP, NADH and reactive oxygen species levels of bacteria. Gene expression was determined using Real Time quantitative PCR. Results We confirmed that exogenous L-leucine increased the killing effect of sarafloxacin on SAR-R and other clinically resistant Salmonella serotypes. Exogenous L-leucine stimulated the metabolic state of bacteria, especially the TCA cycle, which increased the working efficiency of the electron transfer chain and increased the intracellular NADH, ATP concentration, and reactive oxygen species level. Our results suggest that when the metabolism of drug-resistant bacteria is reprogrammed, the bactericidal effect of antibiotics improves. Discussion This study further enhances research in the anti-drug resistance field at the metabolic level and provides theoretical support for solving the current problem of sarafloxacin drug resistance, a unique fluoroquinolone drug for animals and indicating the potential of L-leucine as a new antibiotic adjuvant.